A systematic review on the neurological and psychopathological correlates of pica - Fourie, Lauren (Department of Psychology, 2025)
Pica, the consumption of non-nutritive substances for longer than 30 days, has had several aetiologies reported. These include micronutrient deficiency, psychological and developmental disorders, and neurological and neurochemical pathologies, with a predominant focus in literature on micronutrient deficiency. Thus, a thorough exploration of the possible neurological (i.e., diagnosed conditions, neuroanatomical regions, neuropsychological profiles, neurodevelopmental disorders, neurotransmitter systems) and psychopathological (i.e., diagnosed conditions, psychological mechanism) correlates is needed. Although a recent review on the topic exists, it has not been reported on systematically. The aim of this systematic review (SR) is to firstly, provide a comprehensive overview of the existing research pertaining to neurological and psychopathological correlates of pica. Secondly, to provide a deeper understanding of pica onset and progression and to inform comorbid diagnosis and treatment of pica. Methodology of the review followed the PRISMA 2020 guidelines. Databases searched included PubMed, Scopus, Science Direct, EbscoHost (Academic Search Premier, CINAHL, Health Source: Nursing/Academic Edition, APA PsycArticles, APA PsycInfo, Medline). Methodological evaluation of studies was conducted using the Joanna Briggs Institute (JBI) Critical Appraisal Tool. An adapted JBI checklist was used for each of the study designs including case reports, case series, case control, and cross-sectional designs. 5468 journal articles were identified, 1102 articles were checked using eligibility criteria, and 15 articles were included in the review. Findings showed that the most prevalent neurological conditions correlated to pica included neurodegenerative diseases (Fronto-temporal dementia; Alzheimer's disease and Multi-infarct Dementia), acquired brain injury and stroke. The neuroanatomical regions most associated with pica included the frontal and temporal cortex as well as limbic system structures. Neuropsychological profiles of individuals with pica were in keeping with the neuroanatomical regions described and included semantic memory deficit, aphasia (Transcortical Sensory and Wernicke's) as well as cognitive difficulties following left temporal (verbal learning, memory, and reasoning) and right frontal (cognitive switching) damage. The most prevalent neurodevelopmental disorders associated with pica were Intellectual Disability and Autism-Spectrum Disorder. Successful treatment of pica mainly included serotonin inhibitors or antagonists, indicating a possible correlation between the dysregulation of serotonin neurotransmitters and pica. In addition, the most prevalent psychopathological correlates of pica included OCD, schizophrenia, and depression, with the relief of anxiety being the most prominently reported reason for engaging in pica behaviour. Furthermore, even though these findings prove to be promising, the studies included were predominantly case report or case series, therefore a recommendation for larger scaled studies is warranted.